Efficacy of Transdiagnostic Treatments: A Review of Published Outcome Studies and Future Research Directions - McEvoy, Peter; Nathan, P.; Norton, P. (Springer Publishing Company, 2009)
Theory and evidence relating to biological and psychological vulnerabilities, comorbidity, latent structure, cognitive and behavioral maintaining factors, and treatment outcome suggest that commonalities across emotional disorders may outweigh the differences. Thus, researchers have recently begun evaluating transdiagnostic (or unified) treatment protocols, which target common maintaining factors, by applying them to individuals with multiple disorders or to mixeddiagnosis groups. The aim of this article is to review the efficacy of unified protocols for anxiety and mood disorders. Evidence suggests that unified treatments are associated with symptom improvement, generally perform better than wait-list controls, are associated with improvements in comorbid disorders, and may compare well to diagnosis-specific treatments. Unified protocols are also associated with high client satisfaction, therapeutic alliance, group cohesion, and positive treatment expectations. However, these conclusions are tempered by the small number of studies and methodological limitations. We propose directions for future research.